POLA WORKSHOP MENGGAMBAR PADA NOVEL, REPETISI GARIS DAN WARNA, KEKUATAN KELENTURAN BAMBU - Sujana, I Wayan (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2021)
The purpose of writing 'The Patterns of Wayan Sujana Suklu's Art Workshop' is in an effort to bring the artistic arts that have been designed by the author into the midst of society. The tendency of today's society to want art activities as an effort to meet the needs of self-actualization, and to feel the art process. The forms of art workshops that are typical of the medium and applied aspects are important both practically and theoretically. Why is it necessary to write an art workshop, what are the forms and stages of the art workshop process, then the experience gained from the art workshop process, these three things become topics in writing. Supporting theories and concepts include Nicolas Bourriaud's Relational Aesthetics and the formal principles of art by De Witt H. Parker. In this paper, three patterns of art workshops are presented, namely: Line and Color Repetition, Drawing on Novel, Bamboo Flaxi and Strong.